Efektivitas Layanan Perpustakaan terhadap Penyandang Tunanetra di Panti Sosial Binanetra Tuah Sakato Padang - Annisa, Annisa; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper is aimed at assessing the effectiveness of library services to People with Visual Impairment in Social Institution Bina Netra Tuah Sakato Padang. The method used is descriptive method, that data is collected through observation, interview, and literature study with blind people in the Library users Social Institution Bina Netra Tuah Sakato Padang. Based on the results of this study concluded matters as the following. First, the effectiveness of the services contained in the library Social Institution Bina Netra Tuah Sakato not run well because libraries still provide the services that are still in the stage of a standard or simple and the presence of special facilities should be used for people with visual impairment. Second, there are obstacles: 1) lack of effective services that are applied 2) the lack of budget funds in the provision of facilities and materials in the library collections resulted in the ineffectiveness of the library service. 3) the librarian has a friendly attitude and good, but librarians do not have the educational background of library science. Third, efforts made to overcome the above as follows. 1) provide optimal service and add to the library service, 2) proposed budget for facility improvements and additions to the library collection, 3) conduct training for librarians in order to know the ins and outs of the library and the library is able to manage it well.Keyword: effectiveness of services, library services, blind.